2000
DOI: 10.3171/jns.2000.93.5.0762
|View full text |Cite
|
Sign up to set email alerts
|

Sellar reconstruction with resorbable vicryl patches, gelatin foam, and fibrin glue in transsphenoidal surgery: a 10-year experience with 376 patients

Abstract: Closure of the sella turcica with a synthetic absorbable vicryl patch, gelatin foam, and fibrin glue after transsphenoidal surgery is safe and very effective in preventing postoperative CSF fistulas. The use of this technique obviates the need for a second surgical incision and shortens the operating time. Because of the progressive resorption of the substitute material, the interpretation of postoperative magnetic resonance studies was not significantly hindered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 15 publications
(12 reference statements)
5
72
0
1
Order By: Relevance
“…Black et al reported a higher incidence of postoperative CSF leak in macroadenomas (4.2%), particularly those with suprasellar extension, than microadenomas (0.9%). On the other hand, others did not observe any correlation between pituitary adenoma size and the likelihood of postoperative leak [13].…”
Section: Risk Factors Of Cerebrospinal Fluid Leakmentioning
confidence: 98%
See 2 more Smart Citations
“…Black et al reported a higher incidence of postoperative CSF leak in macroadenomas (4.2%), particularly those with suprasellar extension, than microadenomas (0.9%). On the other hand, others did not observe any correlation between pituitary adenoma size and the likelihood of postoperative leak [13].…”
Section: Risk Factors Of Cerebrospinal Fluid Leakmentioning
confidence: 98%
“…Various studies have investigated the factors that contribute to persistent CSF leak [2,[11][12][13]. Black et al reported a higher incidence of postoperative CSF leak in macroadenomas (4.2%), particularly those with suprasellar extension, than microadenomas (0.9%).…”
Section: Risk Factors Of Cerebrospinal Fluid Leakmentioning
confidence: 99%
See 1 more Smart Citation
“…As displayed in the literature, numerous options for skull base reconstruction after endoscopic endonasal surgery, including both autologous and synthetic materials, have been described to date. [1][2][3][4][5][6][7][8][9][10][11] The primary goal of skull base reconstruction, regardless of surgical technique, includes watertight separation of the intracranial and sinonasal cavities. Failure to achieve these reconstructive goals can result in life-threatening complications such as CSF leak, meningitis, or tension pneumocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Many of these methods evolved from lessons learned from microscopic transsphenoidal approaches and incorporate a wide a range of surgical materials, including autologous fascia, muscle, fat, and bone, as well as various synthetic materials and tissue sealants for multilayered closure. The goal of reconstruction is to reduce the incidence of postoperative complications, such as infection and cerebrospinal fluid (CSF) leak.…”
Section: Introduction Backgroundmentioning
confidence: 99%